A literature review on the causal relationship between Occlusal Factors (OF) and Temporomandibular Disorders (TMD) II: observational analytical epidemiological studies - Acosta-Ortíz, Rodolfo; Rojas-Sarria, Blanca P. (Revista Facultad de Odontología Universidad de Antioquia, 2009)
This is the second article in a series that aims to do a literature review about the causal relationship between occlusal factors (OF) and temporomandibular disorders (TMD). This article presents and analyzes analytic epidemiologic studies, which are positioned higher in the hierarchy of scientific evidence and may offer more concrete conclusions about possible relationships between OF and TMD. The analysis of the studies reported in this article did not find any causal relationship between OFs and TMD development. Although there was an association between some OFs and TMDs, many of them could be better seen as the consequence and not the cause of a TMD. Additionally, even though certain OFs were correlated to TMD signs or symptoms in the longitudinal studies, none of the OFs could be associated with the development of a TMD or any TMD diagnostic categories.